PENGEMBANGAN SISTEM PERPUSTAKAAN SEKOLAH VOKASI UNIVERSITAS PAKUAN BERBASIS WEB - Akbar Sugih Miftahul Huda; Dian Kartika Utami; Alif Diaz Tri Wardhana (Jurnal Riset dan Transformasi Pendidikan, 2026)
The library is a work unit in the form of a place to collect, store, manage, and organize a collection of library materials systematically for use by users as a source of information as well as a fun learning tool. SMK has a library that stores books, final assignments and student journals. There are deficiencies in the Vocational School library, namely the process of handing over or borrowing the library cannot be done at any time. therefore in this development there is an e-book borrowing feature which can only be viewed in PDF form at the time specified by the library admin. In addition, a free library feature for students to submit completed journals/reports to the Pakuan University Vocational School Library as a Graduation Requirement. The Software Development Life Cycle (SDLC) method will be used in this research. This method consists of planning, analysis, design, implementation, testing & integration and maintenance.